2018
DOI: 10.1097/md.0000000000010958
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the microRNA profiles as potential diagnostic probes for oligo- and polymetastatic prognosis of lung metastasis(es) patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Interestingly, recent data suggest that miRNA signatures might display tissue/organ specificity. Osaki et al reported that miR-143-3p expression decreased in a metastatic osteosarcoma cell line (143B) and primary osteosarcoma tissues with lung metastasis [85]. By comparing samples from patients without metastases and sample from those with lung metastases, Sasaki et al showed that increased expression of miR-27a and decreased miR-95-3p and miR-195 expression and miR-133 dysfunction are associated with which cancers develop lung metastasis [86].…”
Section: Genetic Signature Associated To Metastatic Tropism To Thementioning
confidence: 99%
“…Interestingly, recent data suggest that miRNA signatures might display tissue/organ specificity. Osaki et al reported that miR-143-3p expression decreased in a metastatic osteosarcoma cell line (143B) and primary osteosarcoma tissues with lung metastasis [85]. By comparing samples from patients without metastases and sample from those with lung metastases, Sasaki et al showed that increased expression of miR-27a and decreased miR-95-3p and miR-195 expression and miR-133 dysfunction are associated with which cancers develop lung metastasis [86].…”
Section: Genetic Signature Associated To Metastatic Tropism To Thementioning
confidence: 99%
“…Several studies suggested that some genes and microRNA are expressed differently between two states, such as: PECAM1, KDR, PBK, and microRNA-200 family (miR-200b and miR-200c) and so on. [23][24][25][26] With the wide use of advanced imaging, researchers found that oligometastases not only existed in PCa, but also appeared in other cancers (includes bladder cancer, lung cancer, gastric cancer, esophagus cancer, etc.). [27][28][29][30] What's more, researchers found that T A B L E 5 Characteristics of studies included in the systematic review and meta-analysis | 741 surgical resection of the primary tumor may improve quality of patients' life and prolong their survival times who had various oligometastatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Oligometastases (OM) were defined as 1–5 lesions, while patients with 6+ lesions were designated as polymetastatic (PM) as previously described 2,24–26 . For any patients detected to have OM, detailed tumor burden data were collected at three timepoints: first visualization (earliest visualization, but not confirmation of suspicious lesions), confirmation (through biopsy or PET), and first treatment of metastases.…”
Section: Methodsmentioning
confidence: 99%